2021
DOI: 10.3846/jbem.2021.14287
|View full text |Cite
|
Sign up to set email alerts
|

Does the Insurance Sector Really Matter for Economic Growth? Evidence From Central and Eastern European Countries

Abstract: This paper analyses the impact of insurance sector development on economic growth based on a sample that includes 14 Central and Eastern European (CEE) post-transition countries for a period of 19 years, from 1998 to 2016. Considering the presence of cross-section dependence and multiple structural breaks, recently developed panel econometric techniques were employed and led to the following conclusions: (1) life insurance has no significant effect on economic growth in both panel and individual countries, (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The test also showed that there was bidirectional causality for Austria while Slovakia had no causality. Bayar et. al.…”
Section: Review Of the Empirical Literaturementioning
confidence: 99%
“…The test also showed that there was bidirectional causality for Austria while Slovakia had no causality. Bayar et. al.…”
Section: Review Of the Empirical Literaturementioning
confidence: 99%
“…According to Cheston et al (2018) "insurance inclusion is the state of access to and use of appropriate and affordable insurance products for the unserved and underserved". Arguably, existent studies have proved insurance to contribute to economic growth at the macro level and poverty alleviation at the micro level (Bayar et al 2021;Zulfiqar et al 2020). Thus, inclusive insurance can enable poverty alleviation through savings mobilisation for entrepreneurship and reducing people's risk susceptibility (Kim et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is surprising that thorough and in-depth research of this kind is not more prevalent among research subjects, given the significance of the insurance sector in facilitating a wide range of economic transactions. Few studies have examined the connection between insurance and economic growth, with the majority of empirical works on the financial sector concentrating more on the banking industry or the stock market (Ahmed & Bashir, 2016;Bayar & Gavriletea, 2018;Sawadogo et al, 2018;Bayar et al, 2021). This study aims to contribute to the growing empirical inquisitions in the literature by examining the causal relationship between insurance and economic growth in Nigeria.…”
Section: Introductionmentioning
confidence: 99%